Firn layer impact on glacial runoff: a case study at Hofsjökull, Iceland - Braun, Matthias; Hock, Regine; Thorsteinsson, Thorstein; de Woul, Matthias; Johanesson, Tomas; Halldórsdóttir, S. (Hydrological Processes, 2006)
A mass balance-runoff model is applied to Hofsjökull, an 880 km2 ice cap in Iceland, in order to assess the importance of the firn layer for glacial runoff. The model is forced by daily temperature and precipitation data from a nearby meteorological station. Water is routed through the glacier using a linear reservoir model assuming different storage constants for firn, snow and ice. The model is calibrated and validated using mass balance data and satellite-derived snow facies maps. Simulated mass balances and snowline retreats are generally in good agreement with observations. Modelled cumulative mass balance for the entire ice cap over the period 1987/1988 to 2003/2004 is -7.3 m, with uninterrupted negative mass balances since 1993/1994. Perturbing the model with a uniform temperature (+1 K) and precipitation (+10%) increase yields static mass balance sensitivities of -0.95 m a-1 and +0.23 m a-1 respectively. Removing the firn layer under otherwise likewise conditions results in almost unchanged total runoff volumes, but yields a redistribution of discharge within the year. Early summer discharge (June to mid August) is amplified by roughly 5-10%, whereas late-summer/autumn discharge (mid August to November) is reduced by 15-20% as a result of accelerated water flow through the glacial hydrological system. In comparison, applying a climate-model-based temperature and precipitation scenario for Iceland until 2050 results in higher runoff throughout the year, increasing total runoff by roughly one-third. The results emphasize the role of the firn layer in delaying water flow through glaciers, and the influence on discharge seasonality when firn areas shrink in response to climate-change-induced glacier wastage. Copyright © 2006 John Wiley & Sons, Ltd.
UnivIS-Import:2015-04-20:Pub.2006.nat.dgeo.IG.pgfgis.firnla
Keywords: Climate change; Firn; Glacier mass balance; Glacier runoff; Hofsjökull; Iceland; Temperature index model